2022
DOI: 10.1186/s12984-022-01036-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal, kinematic and kinetic assessment of the effects of a foot drop stimulator for home-based rehabilitation of patients with chronic stroke: a randomized clinical trial

Abstract: Background Gait disability affects the daily lives of patients with stroke in both home and community settings. An abnormal foot–ankle position can cause instability on the supporting surface and negatively affect gait. Our research team explored the ability of a portable peroneal nerve-targeting electrical stimulator to improve gait ability by adjusting the foot–ankle position during walking in patients with chronic stroke undergoing home-based rehabilitation. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…A few investigations revealed that the use of neuromuscular electric stimulation (NMES), electric stimulation (ES), or devices for electrical stimulation of the peroneal nerve were ineffective in suppressing muscular spasms (12,25,31); however, these papers were based on trial and error, and it is unclear if the use of such devices may alter the bioelectric. In other words, neither bioelectric nor cell polarities were measured, but we know that timing and amplitude vary between devices and changes in bioelectric are sensitive to timing and amplitude of the devices (24).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few investigations revealed that the use of neuromuscular electric stimulation (NMES), electric stimulation (ES), or devices for electrical stimulation of the peroneal nerve were ineffective in suppressing muscular spasms (12,25,31); however, these papers were based on trial and error, and it is unclear if the use of such devices may alter the bioelectric. In other words, neither bioelectric nor cell polarities were measured, but we know that timing and amplitude vary between devices and changes in bioelectric are sensitive to timing and amplitude of the devices (24).…”
Section: Limitationsmentioning
confidence: 99%
“…Following a database search, 1281 citations were retrieved, of which 27 addressed the topics of this study. Only three of these 27 studies did not show statistically signi cant differences between ES (electric stimulator) and conventional approaches (12,25,31). These studies focused on the decrease of muscular spasm following a stroke or multiple sclerosis.…”
Section: Description Of Studies and Their Characteristicsmentioning
confidence: 99%
“…Наши данные вступают в противоречие с результатами исследования [32], где было получено заметное улучшение функции ходьбы, при этом все пациенты, как и в нашей группе, имели срок впервые возникшего полушарного ишемического инсульта до 6 месяцев . В то же время в исследовании [33] получены улучшения как общих параметров ходьбы, так и специфичной для отвисающей стопы функции голеностопного сустава на амбулаторном этапе реабилитации . При этом все пациенты находились в хронической фазе .…”
Section: Additional Informationunclassified
“…Patients with stroke are unable to dorsiflex or have inadequate dorsiflexion due to triceps spasm and ankle dorsiflexion muscle weakness, resulting in a “circling gait” when walking ( Fernandez-Gonzalez et al, 2016 ; Nikamp et al, 2018 ). The compensatory gait pattern affects balance and walking efficiency, and increases the risk of falls, thus restricting their participation in many activities of daily life and in the community ( de Haart et al, 2004 ; Mao et al, 2022 ). Therefore, it is crucial to discover effective treatments for foot drop that facilitate the recovery of lower limb functions in individuals with hemiplegia, thereby enhancing their quality of life and facilitating reintegration into family and society.…”
Section: Introductionmentioning
confidence: 99%